Empowering Leadership and Teacher Professional Commitment: The Role of Teacher Learning Capacities - Sari Dewi; Adi Rahmat; Helwen Heri (SAINS ORGANISASI, 2023)
This study aims to determine how much influence the empowering leadership has on professional commitment and capability. This study uses a quantitative descriptive approach to measure the influence of empowering leadership has on professional commitment and capability of trust as mediation at senior high school 1 & 2 Tebing tinggi Meranti island. Data analysis that researchers use is a quantitative descriptive method. Meanwhile, to determine the effect of the empowering leadership has on professional commitment and capability of trust as mediation using the SEMPLS 6.0 application. From the results of testing the hypothesis, it can be concluded that empowering leadership has a significant professional commitment on capability, the empowering leadership has a significant professional commitment on capability, professional commitment has a significant positive effect on capability, and capability is proven to be a mediating variable between empowering leadership and professional commitment. This is evidenced by a significant value (p-value) of less than 5%.